A normative study of the raven coloured progressive matrices test for omani hildren aged 5-11 years* - Ali Mahdi Kazem,; Abdulqawi S. Alzubiadi,; Hussaain A. Alkharusi,; Yousif Hasan Yousif,; Abdullah M. Alsarimi,; Sana S. Al-Bulushi,; Fawzia A. Aljamali,; Skreen Al-Mashhdanny,; Omayma B. Al-Busaidi,; Suad Mubarak Al-Fori,; Wedad A. Al-Bahrani,; Basim M. Alshammary, (penerbit ukm, 2009)
Raven’s Coloured Progressive Matrices test has been extensively used across a wide variety of settings in different countries all over the world as a fair culture measure of non-verbal intelligence. The objective of the present study is to extract norms of the test for Omani children. The test was applied on an individual basis on a random sample of 1042 children from different age groups ranging from 5 to 11 years old. All of the estimated psychometric properties including validity, reliability, and norms indicate that the test could be practically utilized when applied in several situations. The study has a number of implications including that the Ministry of Education may use it to diagnose and detect those children with learning difficulties; the Ministry of Health may use it in hospitals to measure the IQ of certain patients in order to make medical decisions. In addition, researchers in psychological and social areas would be able to conduct studies aiming at measuring the intelligence of children.